Deixis Analysis of Gabriel Iglesias’s Utterances in Stand-Up Comedy We Have So Much in Common (2023) - Meliyana, Mila; Laksono, Puji (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
Deixis is discussed in this study. The Greek word for